PENGARUH BEBAN KERJA, KOMPENSASI DAN CAREER DEVELOPMENT TERHADAP KEPUASAN KERJA KARYAWAN GENERASI MILENIAL(Studi Kasus Pada Karyawan Perbankan Swasta di Jakarta Selatan) - Shafa Puti Annisa, (2022)
Banking Digital Transformation has forced banking offices in Indonesia to close. The impact of the closure is a reduction in the number of workers in the banking sector each year. This research is a quantitative study to determine the effect of workload, compensation, and career development on the job satisfaction of private banking employees in South Jakarta. The sample used in this study is 100 millennial generation who work in private banking in South Jakarta. The number of samples was calculated using the Lemeshow formula and taken using the purposive sampling technique. The tests used were the coefficient of determination test, t-test and f-test using SmartPLS 4.0 program. The test results obtained are (1) workload has a positive and significant effect on job satisfaction (2) compensation has a positive and significant effect on job satisfaction (3) career development has a positive and significant effect on job satisfaction (4) workload, compensation and career development simultaneously affect the job satisfaction of private banking employees in South Jakarta.